2016
DOI: 10.1016/j.ssmph.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Contextual generalized trust and immunization against the 2009 A(H1N1) pandemic in the American states: A multilevel approach

Abstract: The aim of the study was to investigate the association between contextual generalized trust and individual-level 2009 A(H1N1) pandemic immunization acceptance. A second aim was to investigate whether knowledge about the A(H1N1) pandemic mediated the association between contextual generalized trust and A(H1N1) immunization acceptance. Data from the National 2009 H1N1 Flu Survey was used. To capture contextual generalized trust, data comes from an aggregation of surveys measuring generalized trust in the Americ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 46 publications
3
20
2
Order By: Relevance
“…Moreover, in line with literature (Rönnerstrand, 2016 ; Sibley et al, 2020 ), there is an increased sense of trust in political institutions in which the interviewees recognize an attitude of care and attention, as well as toward other citizens. Therefore, trust for interviewees is a necessary condition for overcoming the crisis situation.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, in line with literature (Rönnerstrand, 2016 ; Sibley et al, 2020 ), there is an increased sense of trust in political institutions in which the interviewees recognize an attitude of care and attention, as well as toward other citizens. Therefore, trust for interviewees is a necessary condition for overcoming the crisis situation.…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, Rönnerstrand (2016) observed that contextual, generalized trust has been linked to immunization, in line with the literature that argues that being a trustful individual and residing in a community characterized by trust among members influences health and health behavior (Kawachi et al, 1999;Rose, 2000;Hyyppä and Mäki, 2001;Subramanian et al, 2003;Di Napoli et al, 2019b).…”
Section: Trustsupporting
confidence: 67%
“…Evidence on the role of social and civic capital on information acquisition and mobility changes during the COVID-19 pandemic, both voluntary and in response to regulations, is emerging ( Bargain & Aminjonov, 2020 ; Durante, Guiso & Gulino, 2021 ; Borgonovi & Andrieu, 2020 ; Bartscher et al, 2020 ; Barrios et al, 2020 ). Social capital has also been identified as an important asset for individuals and communities during previous pandemics such as the H1N1 pandemic, leading to greater awareness and adoption of health protective behaviors, such as wearing face masks and vaccinating ( Chuang, Huang & Tseng, 2015 ; Rönnerstrand, 2014 ; 2016 ).…”
Section: The Contribution Of Social Capital To Covid-19 Deathsmentioning
confidence: 99%
“…Also, trust makes people prioritize the common good [ 5 ]. Members of societies characterized by high levels of trust tend to take more precautions against an epidemic [ 25 , 26 ] and have higher immunization acceptance [ 27 ], because trust may be a factor prompting people to pay attention to how their own decisions affect disease transmission in the wider community.…”
Section: Literature Reviewmentioning
confidence: 99%